Analysis of income levels and factors influencing the sale of indigenous Papuan vegetables in Sentani Pharaa Market, Jayapura District - Randalinggi, Amos; Mollet, J. Ary; Kaiwai, Hans Z. (Goodwood Publishing, 2025)
Purpose: This study investigates the factors influencing the income of indigenous Papuan vendors at Pharaa Sentani market, Jayapura Regency, in line with Law No. 21 of 2001 on Special Autonomy, which seeks to improve Papuan welfare through economic empowerment. Methodology: A quantitative approach was applied using multiple linear regression analysis. Primary data were collected from 49 vendor respondents through questionnaires. The independent variables analyzed include business capital, length of business, working hours, and education. Results: The analysis shows that business capital, length of business, and education have a significant positive effect on income, contributing 8%, 12.5%, and 30.5%, respectively. Meanwhile, working hours did not significantly influence income, accounting for only 5.8%. Together, the four variables explain 46.8% of income variation, while 53.2% is affected by external factors such as market conditions, social networks, and product quality. Conclusion: The findings highlight that education and business capital are the most decisive factors for income growth. Longer working hours and years in business alone are insufficient without adequate capital and knowledge. Limitations: The study is limited to 49 respondents from one market, which may restrict generalization. Other factors such as cultural norms and supply chain constraints were not considered. Contribution: This research adds to the literature on indigenous economic empowerment and provides recommendations for policymakers to enhance access to education, training, capital, and market infrastructure for Papuan vendors.